Design of Static VAr Compensator using a General Reactive Energy Definition - Liberado, E. V. (2013)
This paper describes a methodology to design Static VAr Compensators (SVC) using the reactive energy definition from Conservative Power Theory. Application of this methodology is presented through simulations of local and distributed compensation approaches. Results show effective compensation of reactive current and load unbalance. Harmonic distortion caused by thyristor controlled reactor has been suitable attenuated by passive filters designed in combination with the SVC.